Pencegahan dan Penanggulangan Perilaku Penyimpangan Seksual Kelompok LGBT Ditinjau dari Perspektif HAM (Analisis Yuridis Peraturan Daerah Kota Bogor Nomor 10 Tahun 2021) - Nur Febriyanti, Heni; Setya Pratiwi, Cekli; Cholidah, Cholidah (UNES Law Review, 2024)
Bogor City has established regulations on LGBT by issuing Regulation Number 10 of 2021. It is necessary to conduct research on the regulation in order to avoid human rights violations. This research focuses on examining the local regulation of Bogor City on LGBT people from a human rights perspective. This research uses normative legal research. The purpose of this study is to determine the conflict of norms that occur between the Bogor City bylaw and the Human Rights Law, identify human rights violations against LGBT people and determine the efforts of judicial review of the bylaw. Regulation No. 10 of 2021 contradicts the basic rights of citizens stipulated in the Human Rights Law and the rights violated in the regulation include the right to human dignity, the judicial review can be done in two ways. Therefore, it is hoped that there is a need for rule reform so that in the basis of formation there are no conflicts of norms that have implications for violations of human rights.